Comparative Study of Effectiveness of Entrepreneurship Education in Malaysian and Nigerian Universities as Perceived by Lecturers - SANI, Abubakar; JAMIL, Hazri (Ilorin Journal of Education, 2024)
The educational systems of Malaysia and Nigeria, as two developing nations, have experienced a significant transformation through the adoption of an entrepreneurship programme as an innovation in their university curricula. This programme is designed to inculcate an entrepreneurial spirit among graduates. Nevertheless, it has been observed that a significant number of university graduates in these two countries remain bereft of this crucial mindset. This discrepancy is likely due to the obstacles that arise during the implementation process, which this current study tries to investigate based on the views of the lecturers. Employing a qualitative methodology and utilizing a rigorous interview protocol, data were gathered from purposively selected ten (10) lecturers from two prestigious public universities in both Malaysia and Nigeria. Again, this number, as well was considered as the sample size of the study. Through a meticulous thematic analysis, the findings on the challenges include, lack of students’ interest, lack of parents’ support, lack of adequate facilities, large number of students, limitation of skills, lack of sufficient funds, students’ not sufficient in communication skills and lack of lecturers’ expertise. Again, on the suggestion to improve the implementation, the findings include, providing preferential treatment to interested students, expansion of skills, increasing the programme’s credit units, prioritizing experiential activities, and providing financial support to students. Therefore, it is recommended for the university to consider these suggestions in reshaping the implementation practices of entrepreneurship education.